Biofuels from algae - Pandey, Ashok; Chang, Jo-Shu; Soccol, Carlos Ricardo; Lee, D. J. (Duu-Jong); Chisti, Yusuf (Biomass, biofuels and biochemicals., 2019)
Biomass, Biofuels and Biochemicals: Biofuels from Algae, Second Edition provides information on strategies for commercial microalgae based biofuel production, including their cultivation, pre-treatment and conversion methods. The book discusses methods for producing microalgal biomass in large scale by outdoor culturing and outlines new technologies for their use. In addition, it explains how modern genetic engineering enables the generation of recombinant strains that generate higher quantities of feedstock. The complete utilization of microalgal biomass, which can also be obtained from valorizing nutrients from wastewater and industrial exhaust gases, can be efficiently converted to energy rich biofuels and high value pharmaceuticals in a well-defined biorefinery.